2017
DOI: 10.1038/s41598-017-01354-7
|View full text |Cite
|
Sign up to set email alerts
|

Self-Selecting Resistive Switching Scheme Using TiO2 Nanorod Arrays

Abstract: In this study, the resistive switching scheme using TiO2 nanorod arrays synthesized by a large-scale and low-cost hydrothermal process was reported. Especially, the nonlinear I–V characteristics of TiO2 nanorod arrays with a nonlinearity of up to ~10, which suppress the leakage current less than 10−4 Acm−2, were demonstrated, exhibiting a self-selecting resistive switching behavior. It provides a simple pathway for integration of RRAM crossbar arrays without additional stacking of active devices. The mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…Therefore, MZN NRs can improve the uniformity of conductive filaments and thus reduce the CV. In this study, we supposed that ionized oxygen vacancies charge and discharge electrons to achieve cycles of the formation and rupture of conductive filaments on the surface of MZN NRs according to the conduction mechanism [8,9,24,25]. Figure 11a shows that the injected electrons were trapped on the NR sidewall with uniform distribution of ionized oxygen vacancies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, MZN NRs can improve the uniformity of conductive filaments and thus reduce the CV. In this study, we supposed that ionized oxygen vacancies charge and discharge electrons to achieve cycles of the formation and rupture of conductive filaments on the surface of MZN NRs according to the conduction mechanism [8,9,24,25]. Figure 11a shows that the injected electrons were trapped on the NR sidewall with uniform distribution of ionized oxygen vacancies.…”
Section: Resultsmentioning
confidence: 99%
“…However, local conduction filament in thin films is diverse in each switching, leading to the non-uniform distribution of switching voltages and current distributions which are crucial to the memory array application. Reducing the dimension of devices and achieving a high packing density are also important [8].…”
Section: Introductionmentioning
confidence: 99%
“…The device (Al/TiO 2 nanowire /Ti) thus fabricated showed reproducible and stable electrical performance with a high OFF/ON ratio that lasted for up to 10 4 s. It was observed that large density of oxygen vacancies at the Ti/TiO 2 interface was generated and that was reported to be the reason for forming free switching. Resistive switching characteristics of TiO 2 nano-rod system were investigated [36]. The TiO 2 nano-rods were synthesized by hydrothermal method on FTO substrate which also acted as a bottom electrode.…”
Section: B Bipolar Resistive Switchingmentioning
confidence: 99%
“…The self-selecting resistive switching in single material provides novel ways to overcome the sneak path issue for RRAM in the crossbar arrays structure. [36].…”
Section: B Bipolar Resistive Switchingmentioning
confidence: 99%
“…A RRAM cell generally is composed of a metal electrode/insulator/metal (MIM) electrode sandwiched structure [3]. Currently, binary metal oxides such as Al 2 O 3 [4][5][6], TiO 2 [7][8][9], HfO x [10], TaO x [11,12], MoO 3 [13], ZnO [14] or NiO [15] have been mainstreaming insulators for RRAM due to their simple structure, controlled composition and compatibility with complementary metal-oxide-semiconductor(CMOS) processes. However, the problems of binary metal oxide-based RRAMs are obvious, such as more sophisticated methods or using expensive equipment, balance of performance parameters of RRAMs which hinder the realization of their practical applications.…”
Section: Introductionmentioning
confidence: 99%